Control of endemic multidrug-resistant Gram-negative bacteria after removal of sinks and implementing a new water-safe policy in an intensive care unit. Issue 3 (March 2018) - Shaw, E.; Gavaldà, L.; Càmara, J.; Gasull, R.; Gallego, S.; Tubau, F.; Granada, R.M.; Ciercoles, P.; Dominguez, M.A.; Mañez, R.; Carratalà, J.; Pujol, M.
Summary: Background: Contaminated handwashing sinks have been identified as reservoirs that can facilitate colonization/infection of patients with multidrug-resistant (MDR) Gram-negative bacteria (GNB) in intensive care units (ICUs). Aim: To assess the impact of removing patients' sinks and implementing other water-safe strategies on the annual rates of ICU-acquired MDR-GNB. Methods: This six-year quasi-experimental study was conducted from January 2011 to December 2016. The intervention was carried out in August 2014 in two adult ICU wards with 12 rooms each. To assess the changes in annual MDR-GNB rates before and after the intervention, we used segmented regression analysis of an interrupted time-series. Crude relative risk (RR) rates were also calculated. Findings: The incidence rates of MDR-GNB were 9.15 and 2.20 per 1000 patient-days in the pre- and post-intervention periods, respectively. This yielded a crude RR of acquiring MDR-GNB of 0.24 (95% confidence interval: 0.17–0.34). A significant change in level was observed between the MDR-GNB rate at the first point of the post-intervention period and the rate predicted by the pre-intervention time trend. Conclusion: The implementation of a new water-safe policy, which included the removal of sinks from all patient rooms, successfully improved the control of MDR-GNB spread in an ICU with endemic infection. Our results support the contribution of sink use with the incidence of MDR-GNB in endemic environments.